Sex and diagnosis specific associations between DNA methylation of the oxytocin receptor gene with emotion processing and temporal-limbic and prefrontal brain volumes in psychotic disorders - Rubin, Leah H. (Biol Psychiatry Cogn Neurosci Neuroimaging, 2015)
BACKGROUND: The oxytocin (OT) system, including receptor epigenetic mechanisms, has been shown to influence emotion processing, especially in females. Whether OT receptor (OXTR) epigenetic alterations occur across psychotic disorders in relation to illness-related disturbances in social cognition and brain anatomy is unknown. METHODS: Participants with affective and nonaffective psychotic disorders (92 women, 75 men) and healthy controls (38 women, 37 men) from the Chicago site of the BSNIP study completed the Penn Emotion Recognition Test (ER-40), a facial emotion recognition task. We measured cytosine methylation at site -934 upstream of the OXTR start codon in DNA from whole blood, and for the first time their relationship with plasma OT levels assessed by enzyme-immunoassay. Volumes of brain regions supporting social cognition were measured from MRI scans using FreeSurfer. RESULTS: Patients with prototypic schizophrenia features showed higher levels of DNA methylation than those with prototypic bipolar features. Methylation was higher in women than men, and was associated with poorer emotion recognition only in female patients and controls. Greater methylation was associated with smaller volumes in temporal-limbic and prefrontal regions associated previously with social cognition, but only in healthy women and females with schizophrenia. CONCLUSION: DNA methylation of the OXTR site -934 was higher in schizophrenia spectrum than bipolar patients. Among patients, it was linked to behavioral deficits in social cognition and neuroanatomic structures known to support emotion processing only in schizophrenia spectrum individuals.